The Role of Regional Government Information Systems (SIPD) in Increasing Financial Accountability and Transparency in Paniai Regency - Karepouwan, Christian Agustinus (Universitas Mohammad Husni Thamrin, 2025)
The development of information technology has brought significant changes in various aspects of government, including regional financial management. Industrial Revolution 5.0 emphasizes the use of automatic technology and artificial intelligence which can increase bureaucratic efficiency and reduce human error in data management. Information systems (IS) are technologically assisted human workforce systems designed to assist with administrative and operational tasks. The development of interactive connections between humans, data, information, technology and algorithms is meant by this. This research aims to analyze the role of the Regional Government Information System (SIPD) in increasing financial accountability and transparency in Paniai Regency, Central Papua Province. SIPD is an information technology-based system implemented to support regional financial management more effectively, efficiently and transparently. The implementation of SIPD takes the form of a website with the aim of making it easier and faster to carry out supervision and evaluation of public services. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation studies. The research results show that the implementation of SIPD in Paniai Regency has had a positive impact in increasing regional financial transparency and facilitating the budget reporting and monitoring process. However, there are still several challenges in its implementation, such as limited human resources who understand the system and technological infrastructure constraints. This research provides recommendations for increasing human resource capacity and improving infrastructure to support the optimization of SIPD implementation.